Identification of detrimental chemicals of plastic products using PCF in the THz regime. (October 2021) - Jibon, Rayhan Habib; Ahmed, Moaz; Hasan, Md. Khaled
Abstract: A square cored PCF (SC-PCF) sensor is proposed in this paper for the purpose of detecting detrimental chemical analytes (DEHP, BPA, and BPS) that are generally found in different plastic products. This SC-PCF sensor is capable of operating in the 1–2 THz regimes. Within this operable range, we found a relatively higher sensitivity of 96.5% along with 95.73% core power fraction, 0.225 numerical aperture, and a lower Aeff of 1.48 × 10 5 μm 2 at 1.9 THz frequency. A tiny confinement loss of 2.68 × 10 −13 cm −1 and effective material loss of 0.008 cm −1 are also evaluated. Besides the present fabrication techniques ensures the feasibility of fabrication for this proposed SC-PCF sensor. These estimated results evinced that our proposed sensor can efficiently be used in terms of the noxious chemical compounds, gas, and bio-sensing applications.